2021
DOI: 10.1002/jsfa.11069
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient nanoscale tapioca starch prepared by high‐speed jet for Cu2+ removal in simulated industrial effluent

Abstract: BACKGROUND Nanoscale tapioca starch (NTS) was successfully developed by high‐speed jet in our previous study. In this study, the adsorption capacity of Cu2+ onto NTS was further discussed. The optimal adsorption conditions (pH, contact time, contact temperature, initial Cu2+ concentration, and adsorbent concentration), adsorption kinetics, isotherms, and thermodynamic were also evaluated. RESULTS The results showed that NTS exhibited excellent performance in adsorption of Cu2+, with adsorption capacities of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…With the increase of contact time, the surface adsorption sites gradually decreased until a saturation state was reached and the adsorption capacity reached equilibrium. 19 Furthermore, the polyphenol absorption capacities of TSNs were ranked as PAC (68.69 mg g −1 ) > CC (33.34 mg g −1 ) > EC (21.14 mg g −1 ), which may be related to the polyphenol molecular weight. This result was consistent with the observation reported previously, 15 where a higher polyphenol adsorption capacity was obtained by starch nanoparticles with a higher polyphenol molecular weight.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…With the increase of contact time, the surface adsorption sites gradually decreased until a saturation state was reached and the adsorption capacity reached equilibrium. 19 Furthermore, the polyphenol absorption capacities of TSNs were ranked as PAC (68.69 mg g −1 ) > CC (33.34 mg g −1 ) > EC (21.14 mg g −1 ), which may be related to the polyphenol molecular weight. This result was consistent with the observation reported previously, 15 where a higher polyphenol adsorption capacity was obtained by starch nanoparticles with a higher polyphenol molecular weight.…”
Section: Resultsmentioning
confidence: 96%
“…The native starch was spherical with a smooth surface and a particle size of 14 600 ± 1200 nm (data not shown), which was similar to that reported in our previous literature. 19,20 The nanostarches were obtained by a HSJ (240 MPa) after pretreatment of micronization with a particle size of 68 ± 3 nm (see Fig. 1a).…”
Section: Micromorphological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The high correlation coefficient (R 2 = 0.9982) showed that the adsorption of Pb(II) on M-NC followed the pseudo-second-order model, meaning that the dominant mechanism of the adsorption process was chemical adsorption instead of physical adsorption. 36 The intraparticle diffusion kinetic plot is illustrated in Fig. 2(d).…”
Section: Adsorption Kineticsmentioning
confidence: 99%